The Correlation Relationship Between Psychological Stress And Starting Speed In The 100-meter Race For Third Year Students Of Athletics Specialty - Saoudi , Aissa; Mansouri , Nabil (sports creativity, 2025)
The purpose of this study is to determine the relationship between the psychological stress and the speed of departure of the runners in the race of 100 meters, by studying the relation between the post-physiological stress and the cognitive and psychological stress with the speed of departure. This study was applied to the third-year students who specialized in athletics, and they were 15 runners and were chosen by the intentionally method. In order to achieve the objectives of the study, the descriptive approach was used which considered as the most suitable approach to the subject of the study, and a physical test was used as tools for the study to measure the starting speed of 30 meters, in addition to the tonometer as the best and most effective method to verify the problematic we gave, where it was found that there is a relationship between the stress and the starting speed in a 100-meter runners, and based on this results, the researchers recommend focusing on psychological preparation and preparing runners for a significant period of time before the competitio